Electrically controlled propagation of laser radiation based on liquid-crystal elements - Rushnova, Iryna I.; Melnikova, Elena Aleksandrovna (Journal of the Belarusian State University. Physics, 2018)
The possibility of creating a two domain liquid crystal element with a planar and homeotropic orientation of the director allowing realization of spatial displacement of the refractive boundary induced by an electric field is demonstrated. Displacement of the refractive interface under the action of an external field in the LC cell with a fragmentary conductive layer provides a controlled linear shift of the light wave trajectory reflected in the conditions of the total internal reflection. The possibility of a controlled angular deflection of a reflected light wave in an NLC element using a conductive layer with the form of an arc is presented. The modified technology to fabricate electrically controlled liquid crystal elements for routing of a polarized light wave is proposed. Application of a photoalignment composite structure comprising two sublayers of nylon-6 and AtA-2 photoalignment azo dye offers high alignment quality value of liquid crystal initial director orientation in cells with a fragmentary conductive layer.
Keywords: nematic liquid crystal; total internal reflection; electrically controlled topology of director orientation; commutation; translation of refractive interface; controlled angular light deflection